The Effect of Transcribing on Elementary Iranian EFL Learners’ Listening Comprehension - Afsharrad, Mohammad; Nafchi, Asghar Moulavi (Dinamika Ilmu: Jurnal Pendidikan, 2015)
This study is motivated by the gap existing between theory and practice in teaching listening. Most of the techniques used to teach listening put more emphasis on top-down processing while listeners’ problems are more of perceptive ones (bottom-up). In order to address the pervasive decoding problem in listening, this study suggests using transcribing exercise as an input enhancement device and investigates its effect on beginning learners’ listening ability. To this end, 31 learners participated in the study. The control group did not have any transcribing practice while the experimental group received transcribing exercise. In the data analysis step, an independent samples t test was employed to compare the two groups. The results show that transcribing has a significant positive effect on beginning learners’ listening comprehension. The findings of the study as well as advantages of transcribing exercise are discussed. Implications of the study and scope for future research are also addressed.